Hambatan Minat Belajar Bahasa Arab dalam Penerapan Quantum Learning pada Siswa Kelas VII Madrasah Tsanawiyah Ma’had Al-Zaytun - Manalu, Samsia; Syaudah, Laely; Iswandi, Irvan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the quantum learning method in Arabic language learning and to identify the barriers to students’ learning interest among seventh-grade students at MTs Ma’had Al-Zaytun. This study employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing using source triangulation. The results showed that the implementation of quantum learning through the TANDUR stages was able to create an active and enjoyable learning atmosphere through the use of songs, educational games, and group activities. This method also increased students’ involvement in Arabic learning. However, several obstacles were still found, such as differences in students’ basic Arabic abilities, passive or introverted student characteristics, and low intrinsic motivation in participating in learning activities. Therefore, the implementation of quantum learning requires adaptive learning strategies based on students’ characteristics in order to achieve more effective learning outcomes.